The impact of media selection on advertising effectiveness an empirical study from the consumer behavior perspective - Christian, Avi; Hidayat, Nila Krisnawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Advertising has been around for more than a century. The development of technology has brought many media for advertising. This gives advertisers more options to choose the best medium for advertising. However, this also brings problems to advertisers, namely to choose the best media for advertising. This study was conducted to determine the impact of media selection on advertising effectiveness, an empirical study from the perspective of consumer behavior. The type of research in this research is descriptive research: single – cross sectional design, quantitative research. This research was conducted in Greater Jakarta with 155 respondents. Data were analyzed using SPSS and PLS. This research study shows that media selectin has a positive significant impact on advertising effectiveness. It shows that media selection is an important part of reaching advertising effectiveness.